1988
DOI: 10.1002/ajh.2830270202
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and natural history of patients with essential thrombocythemia and the Philadelphia chromosome

Abstract: Six women presented with the clinical picture of essential thrombocythemia (ET) without the anemia, marked splenomegaly, and extreme leukocytosis characteristic of chronic myelogenous leukemia (CML). All had the Philadelphia chromosome on karyotype analysis of the bone marrow. Peripheral basophilia was present in four cases, providing a clinical clue that the Philadelphia chromosome might be present. Marrow biopsy showed granulocytic hyperplasia and either small megakaryocytes or sheets of megakaryocytes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 21 publications
(6 reference statements)
1
35
0
1
Order By: Relevance
“…Yet only after progression to accelerated phase were chromosome studies performed which established the diagnoses of CML. The PVSG mandate for karyotyping was stimulated by their experience with six young women who were Philadelphia chromosome positive but otherwise fulfilled diagnostic criteria for ET [7]. These six women all had features that suggested the possibility of CML from the outset, including leukocytosis, leukoerythroblastosis, and/or basophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Yet only after progression to accelerated phase were chromosome studies performed which established the diagnoses of CML. The PVSG mandate for karyotyping was stimulated by their experience with six young women who were Philadelphia chromosome positive but otherwise fulfilled diagnostic criteria for ET [7]. These six women all had features that suggested the possibility of CML from the outset, including leukocytosis, leukoerythroblastosis, and/or basophilia.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, our case differs in that the transcript was similar to the b2a2 transcript with an inserted sequence, the disease resembling ET due to the marked thrombocytosis, absence of splenomegaly, and normal LAP score. Early reports of ET with a Ph chromosome 1 have not included detailed molecular genetic studies but have indicated that the prognosis in ET was similar to that in CML. A later study 13 noted that the BCR/ABL transcript was not detected in four ET cases who were Ph chromosome negative.…”
Section: Discussionmentioning
confidence: 99%
“…Opinions have differed whether the absence of the Philadelphia chromosome (Ph) is required for ET diagnosis. Some [1][2][3] have studied Ph + ET whereas others discuss CML with thrombocythemic onset. 4,5 CML is characterized by leukaemic cells bearing the Philadelphia chromosome, a t(9;22)(q34;q11) reciprocal translocation that results in a BCR/ABL fusion gene and a 210 kDa protein product involving the BCR gene of chromosome 22 and the ABL gene of chromosome 9.…”
Section: Introductionmentioning
confidence: 99%
“…Our results confirm the presence of BCR-ABL positivity by PCR in some patients with ET, albeit at a lower frequency than that reported by Blickstein et al We analyzed peripheral blood samples, but higher frequencies have been reported in bone marrow. Although the presence of the Ph chromosome in ET carries a poor prognosis, 8 the clinical significance of BCR-ABL positivity in Ph-negative ET at various levels of sensitivity remains unclear. The finding of this molecular abnormality by PCR in our patients doesn't seem to imply a diagnosis of CML, as suggested by the absence of clinical features of CML, their long-term uneventful follow-up, and the spontaneous disappearance of BCR-ABL transcripts in one of them.…”
mentioning
confidence: 99%